100 weekend projects anyone can do : easy, practical projects using basic tools and standard materials. (The Family Handyman, 2016)
"Build fashionable, functional, inexpensive indoor and backyard furniture--even if you're a complete beginner. These are realistic projects for the average weekend warrior that require no great skills, just normal tools you already have and easy-to-buy materials available at any home store,"--Amazon.com.